2006
DOI: 10.1049/ip-its:20055012
|View full text |Cite
|
Sign up to set email alerts
|

Driver response to variable message signs-based traffic information

Abstract: This study investigates driver response attitudes to traffic information provided through variable message signs (VMS). It develops VMS driver response models using stated preference data collected through three different survey administration methods: an onsite survey, a mail-back survey, and an Internet-based survey. In the process, it highlights the strengths and limitations of each method in eliciting driver response attitudes to information provision. The use of different media for the survey administrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 8 publications
3
41
0
Order By: Relevance
“…This is considered to be 'active' guidance compared to 'passive' information, where no advice on alternative routes is provided. In general, messages suggesting alternative routes result in higher diversion rates [29]. An alternative way of referring to these terms is prescriptive against descriptive information [33].…”
Section: Message Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is considered to be 'active' guidance compared to 'passive' information, where no advice on alternative routes is provided. In general, messages suggesting alternative routes result in higher diversion rates [29]. An alternative way of referring to these terms is prescriptive against descriptive information [33].…”
Section: Message Characteristicsmentioning
confidence: 99%
“…Ben-Elia et al [43] found that 'inexperienced' drivers would divert more, as they would rely more on the information provided rather than their knowledge of the network. On the other hand, network familiarity allows more for driver diversion, as familiar drivers have knowledge on alternative routes, whether this is approached through the variable of driver experience (years of license acquisition) [42] or not [20,22,27,29,44].…”
Section: Driver Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, there has been a growing trend of providing real time traffic information through VMS board as an instrument for temporal and spatial management of traffic congestion (Peeta et al 2000;Chaterjee et al 2002;Baofeng et al 2005;Bierlaire et al 2006;Maitra, 2007 and2010a). VMS is proven to be cost-effective measure (Adler and Blue 1998;Peeta and Ramos 2006) for mitigating traffic congestion. Many previous investigations showed that, if real time traffic information via roadside VMS was provided to trip makers in some strategically selected locations, then a change in route switching behavior among trip makers and drivers was expected.…”
Section: Introductionmentioning
confidence: 99%
“…Another study reviewed by Nygardhs and Helmers [19] hinted to some Another survey study in Wisconsin indicated that drivers consider VMS useful in reporting weather status and traffic conditions [12]. Peeta and Ramos [20] investigated the drivers' response to traffic information disseminated through VMS and found a strong correlation between VMS message type and the drivers' response.…”
Section: Introductionmentioning
confidence: 99%